THE FAMILY CACHAÇA AGROINDUSTRY - Thomaz, Leandro Gomes Florenço; Thomaz, Douglas Florenço; Ferrarezi Junior, Edemar (Revista Interface Tecnológica, 2022)
In the present work, subjects related to the processing of sugarcane juice were addressed through the use of a small mill system, exploring its derivatives and potential products and by-products. The methodology approached in the gathering of contents through literary bibliographical information of a qualitative nature, demonstrate that the producer of family origins can, even if in a small physical space, obtain profitability and financial return, making available techniques suggesting strategies regarding the obtaining of the raw material, dimensioning of the business, choosing the equipment that will differentiate its final product, namely, processing, bottling and sale, thus tracing the path for the producer to achieve sustainability.
Keywords: Cachaça; Agroindustry; Engenho; Alambic; Sugarcane